Empowering the mobile worker by wearable computing – wearIT@work - Michael Boronowsky; Otthein Herzog; Peter Knackfuß; Michael Lawo (Journal of Telecommunications and Information Technology, 2006)
Currently wearable computing is still a technology of niches and in a laboratory stage. With wearIT@work a project dedicated to applications was launched by the European Commission (EC IP 004216). The first year of the project is nearly over and first results were achieved. In this paper the concept of the project is introduced and first results are presented. As the project strongly follows a user centred design approach much effort was put on first investigations with users in the four application domains of maintenance, production, hospital and fire fighting. Beside this results concerning a wearable computing hardware platform and software framework were achieved.